Spain as a country of asylum under the Franco regime: The reception of Cuban exiles (1961-1963) - Redondo Carrero, Emilio (Historia y Política, 2022)
In early 1961, hundreds of Cubans fleeing from the regime established by Fidel Castro began to arrive in Spain where Franco’s government and several charities were providing aid. The majority of these refugees considered Spain to be a temporary stop on their journey to the United States, but few had the means to reach their destination. As the influx of Cuban refugees increased, intervention from international organizations such as UNHCR and ICEM became necessary. This article presents the results of research on the first stages of a phenomenon that affected 100,000 refugees in little more than a decade. The sources relied upon are mainly from government archives and records kept by the international organizations involved. Based on their analysis, this article aims to quantify this exile, explain the circumstances surrounding their reception in Spain, examine the motivating factors behind the actors’ participation, and analyze the repercussions all of this had on the relations between the Franco administration and the United States.
Keywords: Spain; Franco regime; Cuban refugees; United States; ICEM